2015
DOI: 10.1186/s12936-015-0816-y
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable repellency of Ligusticum sinense (Umbelliferae), a herbal alternative against laboratory populations of Anopheles minimus and Aedes aegypti (Diptera: Culicidae)

Abstract: BackgroundFor personal protection against mosquito bites, user-friendly natural repellents, particularly from plant origin, are considered as a potential alternative to applications currently based on synthetics such as DEET, the standard chemical repellent. This study was carried out in Thailand to evaluate the repellency of Ligusticumsinense hexane extract (LHE) against laboratory Anopheles minimus and Aedes aegypti, the primary vectors of malaria and dengue fever, respectively.MethodsRepellent testing of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…L. chuanxiong rhizome serves as traditional Chinese medicinal herb and its essential oil demonstrated contact toxicity against maize weevils, Sitophilus zeamais LD 50 13.09 μg/adult 22 . The hexane extract of L. sinense rhizomes possessed remarkable repellency in the control of Anopheles minimus and Aedes aegypti which were the primary vectors of malaria and dengue fever Diptera: Culicidae 23 .…”
Section: Repellent Activitymentioning
confidence: 99%
“…L. chuanxiong rhizome serves as traditional Chinese medicinal herb and its essential oil demonstrated contact toxicity against maize weevils, Sitophilus zeamais LD 50 13.09 μg/adult 22 . The hexane extract of L. sinense rhizomes possessed remarkable repellency in the control of Anopheles minimus and Aedes aegypti which were the primary vectors of malaria and dengue fever Diptera: Culicidae 23 .…”
Section: Repellent Activitymentioning
confidence: 99%
“…DEET, applied to the forearm, repelled Aedes aegypti , Anopheles quadrimaculatus , and Anopheles albimanus for 426 min, 96 min, and 87 min, respectively 29 . A 25% volume fraction of DEET in ethanol repelled Aedes aegypti for 8 h 30 . Whereas, Bernier found that a dose of 0.5 mg cm −2 of DEET applied to a muslin cloth patch was active for 24 h. Catnip’s oil is a better spatial repellent than DEET and demonstrated effective topical repellency properties 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Asadollahi et al state, "it has been identified that chemical repellents are not safe for public health " [1]. Besides the fact that every repellent, botanical or synthetic, is a chemical repellent, the sole source cited for this claim is a paper by Sanghong et al [2] promoting the herb Ligusticum sinense as "a herbal alternative" [sic] against mosquitoes. That paper not only does not test the safety of "chemical repellents" at all, but also actually states that DEET is "considered safe, " and that the rare, toxic effects attributed to it "have been described mainly after misapplication. "…”
Section: Main Textmentioning
confidence: 99%
“…Even if Asadollahi et al were confused about the nature of the repellent-insecticide resistance correlation, there is no basis for them to falsely claim that synthetic repellents differ from natural repellents in this regard. Their sources for the claim are again the paper by Sanghong et al [2], which does not state anything relating to the matter, and Govindaarajan et al [6], an article claiming Zingiber nimmonii is "an eco-friendly tool" against mosquitoes, and which, while also making debunked or incorrect claims about DEET, clearly states that the issues of ecological disruption are due to insecticides, not repellents.…”
Section: Main Textmentioning
confidence: 99%